THE BALANCED SCORECARD: MAKSIMALISASI EMPAT PERSPEKTIF STRATEGIS ASURANSI SYARIAH - NETTA AGUSTI (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2018)
Past research on the application of performance appraisal using the balanced scorecard (BSC) has been widely applied in conventional and Islamic financial institutions, while for non-bank financial institutions tend to be rare. This study aims to assess performance using the BSC method of performance appraisal of Islamic financial institutions in the non-bank PT. Asuransi Takaful Umum Padang Branch. During this time, PT. Asuransi Takaful Umum Padang Branch using the system GPA (Grade Point Average) in performance assessment. GPA rated yet positioned to assess the overall performance of the organization because it is more focused on the internal side of the employees. BSC is a measurement tool that is not only viewed from the financial side, but overall a good non-financial, internal, and external companies. This research uses triangulation concurrent study the research method that combines qualitative and quantitative research methods in a balanced way. The conclusion from this study is that the performance of PT. Asuransi Takaful Umum Padang Branch can be said to be very good with a total score of 89.25% votes. With the weight of the financial perspective in the company's financial condition can be said to be very good with a score of 92.23%, the customer perspective in the position to settle with a score of 76.42% votes, internal business process perspective are in very good condition, whereby this perspective provides assessment score of 100%, as well as the learning and growth perspective in very good condition with a total score of votes obtained by 89.41%.